Moodle-Based Course as a Tool to Support Teaching ESP Class Online - Tonenchuk, Tetiana (Видавничий дім «Гельветика», 2023)
The article explores the transformative impact of technology on education, specifically focusing on the role of Moodle Learning Management System in refining English for Specific Purposes (ESP) courses. The aim of the research is to examine the benefits of a Moodle-based course as an online instrument to support learning English for Specific Purposes and to study students’ feedback regarding Moodle course effectiveness. The widespread use of platforms like Moodle in higher education, its benefits in facilitating teacher-student interaction and managing learning processes, and its alignment with contemporary teaching strategies are highlighted. The article provides an overview of the benefits of using Moodle in ESP courses, supported by empirical evidence and student feedback, emphasizing its role in modernizing and enriching the educational process. The advantages of Moodle Course Management Platform for teachers as an efficient organizational and assessment tool are described. Moodle supports course planning and management, assists in teaching different learning styles online, helps cope with the problems that can arise. The study also highlights the significance of the shift from conventional teaching methods to more learner-centered, available due to technologically driven educational environments. Flexible learning, accessibility, and a higher level of student autonomy are among the most appreciated benefits for students. The results of the survey in the form of a questionnaire helped to summarize the feedback on the effectiveness of the Moodle course from 2nd-year Software Engineering students taking the ESP course at Yuriy Fedkovych Chernivtsi National University. The respondents emphasized the course relevance to their future professions, its ability to improve language skills, and its practical orientation. Students confirmed high levels of motivation, autonomy, and engagement with the course content. Moodle's role in complementing traditional classes, fostering language and problem-solving abilities is also stated. It is stressed that educators need to be ready to adapt and integrate new teaching methods to address evolving learning needs in the digital era.
Keywords: Moodle-based course; teaching methods; flexible learning; motivation; autonomy